Atrial Premature Beats Predict Atrial Fibrillation in Cryptogenic Stroke. Issue 4 (April 2015) - Gladstone, David J.; Dorian, Paul; Spring, Melanie; Panzov, Val; Mamdani, Muhammad; Healey, Jeff S.; Thorpe, Kevin E.; Aviv, R.; Boyle, K.; Blakely, J.; Cote, R.; Hall, J.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Many ischemic strokes or transient ischemic attacks are labeled cryptogenic but may have undetected atrial fibrillation (AF). We sought to identify those most likely to have subclinical AF. Methods— We prospectively studied patients with cryptogenic stroke or transient ischemic attack aged ≥55 years in sinus rhythm, without known AF, enrolled in the intervention arm of the 30 Day Event Monitoring Belt for Recording Atrial Fibrillation After a Cerebral Ischemic Event (EMBRACE) trial. Participants underwent baseline 24-hour Holter ECG poststroke; if AF was not detected, they were randomly assigned to 30-day ECG monitoring with an AF auto-detect external loop recorder. Multivariable logistic regression assessed the association between baseline variables (Holter-detected atrial premature beats [APBs], runs of atrial tachycardia, age, and left atrial enlargement) and subsequent AF detection. Results— Among 237 participants, the median baseline Holter APB count/24 h was 629 (interquartile range, 142–1973) among those who subsequently had AF detected versus 45 (interquartile range, 14–250) in those without AF (P<0.001). APB count was the only significant predictor of AF detection by 30-day ECG (P<0.0001), and at 90 days (P=0.0017) and 2 years (P=0.0027). Compared with the 16% overall 90-day AF detection rate, the probability of AF increased from <9% among patients with <100 APBs/24 h to 9% to 24% in those with 100 to 499 APBs/24 h, 25% to 37% with 500 to 999 APBs/24 h, 37% to 40% with 1000 to 1499 APBs/24 h, and 40% beyond 1500 APBs/24 h. Conclusions— Among older cryptogenic stroke or transient ischemic attack patients, the number of APBs on a routine 24-hour Holter ECG was a strong dose-dependent independent predictor of prevalent subclinical AF. Those with frequent APBs have a high probability of AF and represent ideal candidates for prolonged ECG monitoring for AF detection. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00846924.